신선농산물 수출의 결정요인과 지원 효과 분석 - 문한필 (한국농촌경제연구원, 2012)
This paper analyzes what factors affect Korea's agricultural export. With a dataset of agricultural export for the period of 2003~2009 and several explanatory variables, we specify an export equation derived from the gravity model, and then estimate it using the random-effect panel Tobit. The main findings are as follows: first, Korean agricultural exports have increased faster and greater in bigger markets with respect to GDP. Second, the distance from Korea or transportation cost is a critical factor determining the agricultural export. Third, the export support programs are proved to play a crucial role in boosting the export of fresh agricultural products. Fourth, the effect of relative exchange rates on the agricultural export is shown to be ambiguous or inconsistent from product to product. Finally, the number of Korean expatriates in foreign markets has a positive effect on the export performance.
Keywords: 중력모형; 확률효과 패널토빗; 정부 지원정책; gravity model; random-effect panel Tobit; government support strategies